The Effect of Hydrogen Embrittlement on the Localized Plastic Deformation of Aluminum Alloy - Bochkareva A. V. Anna Valentinovna; Lunev A. G. Alexey Gennadievich; Barannikova S. Svetlana; Gorbatenko V. Vadim Vladimirovich; Shlyakhova G. Galina Vitaljevna; Zuev L. Lev Borisovich (2015, 2015)
Title screen